2017
DOI: 10.1186/s13717-017-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of farmers’ adoption of land management practices in Gelana sub-watershed of Northern highlands of Ethiopia

Abstract: Introduction: Soil erosion is the major environmental problem in Ethiopia. In response to this problem, the country has been in continuous struggle to adopt land management practices. Therefore, the objective of this study was to investigate the determinants of farmers' adoption of land management practice in the Gelana sub-watershed, Northern highlands of Ethiopia. Methods: The data was collected from 176 randomly selected farming households using a survey questionnaire and was analyzed using multinomial logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 26 publications
16
60
0
Order By: Relevance
“…The LULC change is particularly severe in the highlands of Ethiopia where rain-fed subsistence agriculture is the source of livelihood and the base of economic development (Garedew, Sandewall, & Soderberg, 2012). The most proximate implication and negative consequence of this rapid LULC change in the highland areas is severe environmental degradation in the form of soil erosion, soil quality deterioration, loss of biodiversity, habitat distraction and species transfer, and decreasing availability of water (Wubie et al, 2016, Miheretu & Assefa, 2017, Hassen & Assen, 2017Hassen, Mohammed, Assefa, & Tena, 2015;Tsehaye & Mohammed, 2013). Moreover, a study by Minale and Rao (2012) indicated that LULC change has significantly caused local and regional climate change in the north-western highland of Ethiopia.…”
mentioning
confidence: 99%
“…The LULC change is particularly severe in the highlands of Ethiopia where rain-fed subsistence agriculture is the source of livelihood and the base of economic development (Garedew, Sandewall, & Soderberg, 2012). The most proximate implication and negative consequence of this rapid LULC change in the highland areas is severe environmental degradation in the form of soil erosion, soil quality deterioration, loss of biodiversity, habitat distraction and species transfer, and decreasing availability of water (Wubie et al, 2016, Miheretu & Assefa, 2017, Hassen & Assen, 2017Hassen, Mohammed, Assefa, & Tena, 2015;Tsehaye & Mohammed, 2013). Moreover, a study by Minale and Rao (2012) indicated that LULC change has significantly caused local and regional climate change in the north-western highland of Ethiopia.…”
mentioning
confidence: 99%
“…However, agriculture in Ethiopia is characterized by low productivity (Weldemariam et al, 2013;Abebe & Sewnet, 2014), and consequently cannot cover the food requirements of the country's population (Adimassu et al, 2014). Factors attributing to the low level of agricultural productivity and food insecurity in Ethiopia include land degradation, climatic change and variability, low application of inputs and political instability (Anley et al, 2007;Miheretu & Yimer, 2017).…”
Section: Land Degradation In the Highlands Of Ethiopiamentioning
confidence: 99%
“…In this regard, physical structures are often poorly adopted, hardly maintained and sometimes even removed by farmers (Kassie et al, 2010). As a result, land degradation has continued to be a critical threat to Ethiopian agriculture and to attaining the country's food security targets (Mengistu et al, 2015;Nedessa et al, 2015;Miheretu & Yimer, 2017). Research over the past decades revealed that adoption and implementation of SLM practices by Ethiopian farmers is constrained by personal, socioeconomic, biophysical and institutional factors (Asrat et al, 2004;Shiferaw et al, 2009;Adimassu et al, 2012;Abebe & Sewnet, 2014;Teshome et al, 2016a).…”
Section: Sustainable Land Management (Slm) In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation
“…The MNL model estimates the likelihood of adoption of non-reference categories against a reference (base) category in terms of relative risk ratio (RRR) [27]. The other reason for choosing this model is that this has been more commonly used in recent studies [27][28][29][30]. Having three farming practices in place, farmers can choose the one they prefer the most from the three alternatives.…”
Section: Analytical Modelmentioning
confidence: 99%